2011
DOI: 10.1103/physreva.83.042103
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of decoherence from an environmental perspective

Abstract: For the case of phase damping (pure decoherence) we investigate the extent to which environmental traits are imprinted on an open quantum system. The dynamics is described using the quantum channel approach. We study what the knowledge of the channel may reveal about the nature of its underlying dynamics and, conversely, what the dynamics tells us about how to consistently model the environment. We find that for a Markov phase-damping channel, that is, a channel compatible with a time-continuous Markovian evol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 25 publications
0
38
0
Order By: Relevance
“…Recall that pure dephasing of an open quantum system in the basis {|n } implies a controlled-unitary form U tot (t) = e −iHtott/ = n |n n| ⊗ U n (t) of the total propagator [44]. Here, U n (t) = e −iHnt/ with H n = n|H tot |n are system-state-dependent propagators for the environment (see also [45]).…”
Section: Random Unitary Representationsmentioning
confidence: 99%
“…Recall that pure dephasing of an open quantum system in the basis {|n } implies a controlled-unitary form U tot (t) = e −iHtott/ = n |n n| ⊗ U n (t) of the total propagator [44]. Here, U n (t) = e −iHnt/ with H n = n|H tot |n are system-state-dependent propagators for the environment (see also [45]).…”
Section: Random Unitary Representationsmentioning
confidence: 99%
“…On the other hand, when the environment is instead described as a collection of several fluctuators, the QFI is has two local maxima, whose positions drift towards the boundaries of the interval [0. 5,2] as N is increased. The largest quantum signal-to-noise ratio is obtained for brown noise, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in the case of phase damping, i.e. pure dephasing, it has been shown that the interaction of a quantum system with a quantum bath can be written in terms of a random unitary evolution driven by a classical stochastic process [4,5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Helm et al developed a geometrical measurement by using the Bloch sphere picture to determine the non-RU channels [7,8]. In this paper a new method is presented using expansion of considerable state based on Hamiltonian's eigenvalues to investigate the non-RU dynamics.…”
Section: Introductionmentioning
confidence: 99%